The last kids on Earth and the monster dimension - Brallier, Max (Brallier, Max. Last kids on Earth, 2023)
"The last kids may have escaped the forbidden fortress by the skin of their teeth, but there isn't much to celebrate. Thrull has what he needs to complete the Tower, Rezzoch will most certainly come to Earth, and the world as they know it will cease to exist. Except Jack's Cosmic Hand is now even more powerful than he realized, and it might just be able to stop the inevitable from happening. To get the answers he seeks, he'll need to travel farther than he's ever been. He must go . . . to the monster dimension" --